2020
DOI: 10.1371/journal.pmed.1003225
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the risk of narcolepsy in children in England 8 years after receipt of the AS03-adjuvanted H1N1 pandemic vaccine: A case-coverage study

Abstract: Background Early studies of narcolepsy after AS03-adjuvanted pandemic A/H1N12009 vaccine (Pandemrix) could not define the duration of elevated risk post-vaccination nor the risk in children aged under 5 years who may not present until much older. Methods/Findings Clinical information and sleep test results, extracted from hospital notes at 3 large pediatric sleep centers in England between September 2017 and June 2018 for narcolepsy cases aged 4–19 years with symptom on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Booster vaccination is an effective way to attenuate NAbs and reorganize immune resistance. [ 32 ] However, owing to differences in individual immunity, some vaccinated individuals lose the protection of NAbs before booster vaccination, and this window period may be long. Hence, an accurate, rapid, and easy‐to‐operate method for detecting anti‐SARS‐CoV‐2 NAbs is the key to guiding individuals to schedule booster doses and maintain effective resistance against SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Booster vaccination is an effective way to attenuate NAbs and reorganize immune resistance. [ 32 ] However, owing to differences in individual immunity, some vaccinated individuals lose the protection of NAbs before booster vaccination, and this window period may be long. Hence, an accurate, rapid, and easy‐to‐operate method for detecting anti‐SARS‐CoV‐2 NAbs is the key to guiding individuals to schedule booster doses and maintain effective resistance against SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a modelling study of de novo European cases concluded that the NT1 peak in children detected in 2013 (thus in the absence of recent Pandemrix vaccination), was most likely triggered by other risk factors, such as viral infections caused by H1N1 recirculation, or circulation of other/new influenza strains, e.g., influenza B (55). A recent study by Stowe et al shows that an increased risk of NT1 associated with Pandemrix vaccination was "confined to those with onset within the first 12 months with a return to baseline thereafter" (56). This limited (~1 year) timeframe in which the vaccine could be linked to NT1 onsets thus suggests that thereafter other risk factors would have become more likely causes.…”
Section: Role Of Natural Infectionmentioning
confidence: 99%
“…A recent study by Stowe et al. shows that an increased risk of NT1 associated with Pandemrix vaccination was “confined to those with onset within the first 12 months with a return to baseline thereafter” ( 56 ). This limited (~1 year) timeframe in which the vaccine could be linked to NT1 onsets thus suggests that thereafter other risk factors would have become more likely causes.…”
Section: Pharmacoepidemiological Evidencementioning
confidence: 99%
“…Vaccines have been recalled in the past after adverse effects in children were identified when the vaccine was already in routine use (Collignon, Doshi, and Jefferson 2010). In some cases, the adverse effects occurred many months after vaccine administration (Jamrozik et al 2021;Stowe et al 2020). The lack of long-term safety data therefore warrants caution about vaccinating children against COVID-19.…”
Section: Objection 2: Known Risks and Unknown Long-term Vaccine Safet...mentioning
confidence: 99%